Interleukin-6 and interleukin-17 gene polymorphism association with celiac disease in children - Akbulut, Ulaş Emre; Çebi, Alper Han; Sağ, Elif; İkbal, Mevlit; Çakır, Murat (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: This study aimed to investigate polymorphisms in the genes responsible for encoding cytokines interleukin-6 (IL-6) (-572G/C) (rs1800796) and IL-17 (-197A/G) (rs2275913) in patients with celiac disease (CD). We further aimed to investigate the relationship between CD symptoms and histopathological findings and the relationship between these polymorphisms. Materials and Methods: We compared the results with those of healthy control subjects to establish whether any of the polymorphisms are involved in the susceptibility to CD. Eighty-four patients with CD and 83 healthy controls were enrolled in this study. Children with CD were divided into two groups depending on whether their symptoms were typical or atypical. The IL-6 (-572G/C) and IL-17 (-197A/G) polymorphisms were genotyped based on a polymerase chain reaction coupled with restriction fragment length polymorphism. Results: Significant differences for the IL-6 (-572G/C) polymorphism were observed between patients with CD and controls (p=0.018, odds ratio (OR): 5.47, 95% confidence interval (CI): 1.161-25.800). No statistically significant association was observed between the IL-17 (-197A/G) polymorphism and CD (p>0.05). In addition, the symptoms and histopathological findings of children with CD were not related to either of the polymorphisms. Conclusion: The results of our study indicate that the IL-6 (-572G/C) polymorphism may play a role in susceptibility to CD. Cite this article as: Akbulut UE, Çebi AH, Sağ E, İkbal M, Çakır M. Interleukin-6 and interleukin-17 gene polymorphism association with celiac disease in children. Turk J Gastroenterol 2017; 28: 471-5.